Sulfur degassing at Erta Ale (Ethiopia) and Masaya (Nicaragua) volcanoes: Implications for degassing processes and oxygen fugacities of basaltic systems. (2nd October 2013) - de, J. M.; Fischer, T. P.; Sharp, Z. D.; King, P. L.; Wilke, M.; Botcharnikov, R. E.; Cottrell, E.; Zelenski, M.; Marty, B.; Klimm, K.; Rivard, C.; Ayalew, D.; et al.
<x xml:space="preserve">Abstract</x> [1] We investigate the relationship between sulfur and oxygen fugacity at Erta Ale and Masaya volcanoes. Oxygen fugacity was assessed utilizing Fe3+/∑Fe and major element compositions measured in olivine‐hosted melt inclusions and matrix glasses. Erta Ale melts have Fe3+/∑Fe of 0.15–0.16, reflecting fO2 of ΔQFM 0.0 ± 0.3, which is indistinguishable from fO2 calculated from CO2/CO ratios in high‐temperature gases. Masaya is more oxidized at ΔQFM +1.7 ± 0.4, typical of arc settings. Sulfur isotope compositions of gases and scoria at Erta Ale (δ34Sgas − 0.5‰; δ34Sscoria + 0.9‰) and Masaya (δ34Sgas + 4.8‰; δ34Sscoria + 7.4‰) reflect distinct sulfur sources, as well as isotopic fractionation during degassing (equilibrium and kinetic fractionation effects). Sulfur speciation in melts plays an important role in isotope fractionation during degassing and S6+/∑S is <0.07 in Erta Ale melt inclusions compared to >0.67 in Masaya melt inclusions. No change is observed in Fe3+/∑Fe or S6+/∑S with extent of S degassing at Erta Ale, indicating negligible effect on fO2, and further suggesting that H2S is the dominant gas species exsolved from the S2−‐rich melt (i.e., no redistribution of electrons). High SO2/H2S observed in Erta Ale gas emissions is due to gas re‐equilibration at low pressure and fixed fO2. Sulfur budget considerations indicate that the majority of S injected into the systems is emitted as gas, which is therefore representative of the magmatic S isotope composition. The composition of the Masaya gas plume (+4.8‰) cannot be explained by fractionation effects but rather reflects recycling of high δ34S oxidized sulfur through the subduction zone.